(3QSGdI efHFI aj Md ZhGeV dG GdLfS hGdJHQFIs - (3SdjeGf GafOj ajVj GdJhajbjs ((3YKeGf Hf eMeO GdbGQUj s)
(3ChdgG (B:s
(3hHYO, ajbhd CMO GdWdHI ajeG QhGg hfbdg SdjeGf ajVj GdJhajbj aj GdOhdI GdYdjI GdecedI s
(3BNQgG (B:s
(3aJCcO THg GdehUha HGdeVGa aCYWi aj GdCeKdI Mce GdeVGa daXkG aUGQ ef CbSGe GdeYQH hbO Je eG CQOfGg ef EjQGOg ef ZjQ JWhjd hdG RjGOI s
(3HChdgG bQGAI eaJj RGOgs
(3cJHJ Hbde ajg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B145 s
Keywords: (3GdfMhs